Global versus Local Asset Pricing: A New Test of Market Integration - Hau, Harald (Review of Financial Studies, 2011)
[Should capital cost calculations be based on a global or local market benchmark? The December 2000 redefinition of the Morgan Stanley Capital International (MSCI) global equity index was a natural experiment addressing this question. It is argued that this event triggered a portfolio shift (by index funds) large enough to affect the residual asset supplies constituting the global and local market benchmarks of all actively managed capital. Changes in the market benchmarks imply distinct and predictable changes to global and local stock betas. Exploring whether global or local beta changes best explain the cross-section of event returns reveals that stocks in developed markets are priced globally and not locally.]